The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1186/s41077-017-0057-y
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the impact of intensive care unit mattress compressibility during CPR: a simulation-based study

Abstract: BackgroundThe depth of chest compression (CC) during cardiac arrest is associated with patient survival and good neurological outcomes. Previous studies showed that mattress compression can alter the amount of CCs given with adequate depth. We aim to quantify the amount of mattress compressibility on two types of ICU mattresses and explore the effect of memory foam mattress use and a backboard on mattress compression depth and effect of feedback source on effective compression depth.MethodsThe study utilizes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 38 publications
(59 reference statements)
0
22
0
1
Order By: Relevance
“…Survival and neurological outcome of the patient are associated with other factors, such as time to administer epinephrine, time to defibrillate (for shockable rhythms) and underlying conditions of the victims. 29–31 In addition, CPR quality is also influenced by factors other than training, such as the type of mattress on which the patient was put, 32 the use of backboard 33 and height of the CPR providers. 34 At present, it is not practical to account for all of these confounding factors in a trial-based economic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Survival and neurological outcome of the patient are associated with other factors, such as time to administer epinephrine, time to defibrillate (for shockable rhythms) and underlying conditions of the victims. 29–31 In addition, CPR quality is also influenced by factors other than training, such as the type of mattress on which the patient was put, 32 the use of backboard 33 and height of the CPR providers. 34 At present, it is not practical to account for all of these confounding factors in a trial-based economic evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…26 Physicians and other CPR providers struggle to achieve highquality CCs. 2,[7][8][9][10] Past studies have evaluated the factors that may have contributed in decreasing CC quality, such as providing CPR on a mattress. Mattresses compress during CPR.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Studies with simulated and real cardiac arrest cases have shown that, despite CPR training and its widespread use, CC providers struggle to achieve high-quality CCs and the post-CPR survival rates remain low. 2,[7][8][9][10] Many studies focused on this problem and aimed to identify the factors influencing the CC quality. The support surface is one of these factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…90 , 97 , 101 , 102 , 103 , 104 , 105 CPR feedback devices that account for mattress compression (eg, the use of dual accelerometers or increasing compression depth targets) can help CPR providers ensure adequate compression depth when CPR is performed on a mattress. 95 , 99 , 101 , 103 , 105 , 106 …”
Section: Cpr Sequencementioning
confidence: 99%